BCL7B, a predictor of poor prognosis of pancreatic cancers, promotes cell motility and invasion by influencing CREB signaling - Taniuchi, Keisuke (Am J Cancer Res, 2018)
The functions of B-cell CLL/lymphoma 7B (BCL7B) are unknown and the protein lacks any known functional domains. The aim of this study was to investigate the role of BCL7B in the motility and invasiveness of pancreatic cancer cells. Immunohistochemistry was performed to determine whether high BCL7B expression in human pancreatic cancer tissues is correlated with poor prognosis. High BCL7B expression was an independent predictor of worse overall survival of pancreatic cancer patients. Immunocytochemistry showed that BCL7B was accumulated in cell protrusions of migrating pancreatic cancer cells. Knockdown of BCL7B inhibited the motility and invasiveness of pancreatic cancer cells through a decrease in cell protrusions. Phosphoprotein array analysis was performed to determine BCL7B-associated intracellular signaling pathways. Suppression of BCL7B increased phosphorylated CREB expression in pancreatic cancer cells, and knockdown of CREB promoted the motility and invasiveness by increasing cell protrusions. The combined data suggest that BCL7B promotes pancreatic cancer cell motility and invasion through a signaling pathway that involves dephosphorylation of CREB.